On UrysohnBiclosure Spaces - Darwesh, Halgwrd M.; Khalaf, Alias B. (Sulaimani Journal for Pure and Applied Sciences, 2013)
The purpose of this paper is to introduce the concept of Urysohn biclosure space; also we investigate some of its basic properties and relationships with some other known space such as T2- biclosure space, regular biclosure space.
Keywords: closure operator closure space biclosure space urysohn biclosure space